The Design of Eco-friendly Resort, Asu Island (Organic Architecture) (International Journal of Architecture and Urbanism, 2022)
This study aims to design an eco-friendly resort based on an organic architecture approach on Asu Island, Sirombu District, West Nias Regency, North Sumatra Province. The design with an organic architectural approach aims to create a space that can harmonize the indoor space with the outdoor space and can provide a space experience close to nature for resort users. In more detail, the design of eco-friendly resorts on Asu Island aims to meet tourist accommodation needs, facilitate space with attention to tourists, and analyze energy sources and utility systems on Asu Island. The site's location is right on the edge of the sea coast off Asu Island, Sirombu District, West Nias Regency, and is directly opposite the Indian Ocean. The site location selection method is measured from indicators including view, surrounding function, environment, soil condition, an overview of city structure, and accessibility. The location selection for the site was chosen based on several considerations such as view, the location of the resort that is separated from the city crowd, tourist convenience, searching for site locations via google maps and conducting direct surveys to determine site conditions. The approach used in this design is a literature study, a user approach by searching for user room data in resort design, and field studies that are directly carried out to review the condition of the site and the area around the site